Effect of Fish Meal Substitution with Black Soldier Fly (Hermetia illucens) on Growth Performance, Feed Stability, Blood Biochemistry, and Liver and Gut Morphology of Siamese Fighting Fish (Betta splendens) - Zulhisyam Abdul Kari; Guillermo Téllez-Isaías; Noor Khalidah Abdul Hamid; Nor Dini Rusli; Khairiyah Mat; Suniza Anis Mohamad Sukri; Muhammad Anamul Kabir; Ahmad Razali Ishak; Nazri Che Dom; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Martina Irwan Khoo; et al. (Aquaculture Nutrition)
Insects such as black soldier fly larvae (BSFL) are gaining interest among researchers and the aquafeed industry due to the fluctuating price and supply of fish meal (FM). This study evaluated the growth performance, feed stability, blood biochemistry, and liver and gut morphology of Betta splendens using BSFL as an alternative to FM. Five formulated diets were prepared: 0% BSFL, 6.5% BSFL, 13% BSFL, 19.5% BSFL, and 24.5% BSFL. The expansion rate, pellet durability index, floatability, bulk density, and water stability of the prepared feed have been assessed. Except for the diameter of the feed, all the parameters studied differed significantly (p<0.05) across the experimental diets. After 60 days, the fish fed with 13% BSFL had the highest final length, final weight, net weight gain, specific growth rate, weight gain, and gastrointestinal weight, with mean and standard deviation values of 3.97±0.43 cm, 3.95±0.1 g, 2.78±0.1 g, 4.63±0.17, 4.65±0.13, 237.26±7.9%, and 0.04±0.01 mg, respectively. Similar blood haematology and biochemical properties, including corpuscular volume, lymphocytes, white blood cells, red blood cells, haematocrit, albumin, and alkaline phosphatase, were the highest (p<0.05) in the 13% BSFL diet group compared to the other treatment groups. In addition, BSFL had a significant impact (p<0.05) on villus length, width, and crypt depth for the anterior and posterior guts of B. splendens. The 13% BSFL diet group had an intact epithelial barrier in the goblet cell arrangement and a well-organized villus structure and tunica muscularis, compared to the other treatment groups. Furthermore, the liver cell was altered with different BSFL inclusions; the 13% FM group demonstrated better nuclei and cytoplasm structure than the other treatment groups. In conclusion, replacing 13% FM with BSFL could improve the growth performance, blood parameters, and liver and intestine morphology of B. splendens, thus providing a promising alternative diet for ornamental freshwater fish.